D2 dopamine receptors and the striatopallidal pathway modulate L-DOPA-induced dyskinesia in the mouse - Sáez, María (2023)
L-DOPA-induced dyskinesia (LID) remains a major complication of Parkinson's disease management for which better therapies are necessary. The contribution of the striatonigral direct pathway to LID is widely acknowledged but whether the striatopallidal pathway is involved remains debated. Selective optogenetic stimulation of striatonigral axon terminals induces dyskinesia in mice rendered hemiparkinsonian with the toxin 6-hydroxydopamine (6-OHDA). Here we show that optogenetically-induced dyskinesia is increased by the D2-type dopamine receptor agonist quinpirole. Although the quinpirole effect may be mediated by D2 receptor stimulation in striatopallidal neurons, alternative mechanisms may be responsible as well. To selectively modulate the striatopallidal pathway, we selectively expressed channelrhodopsin-2 (ChR2) in D2 receptor expressing neurons by crossing D2-Cre and ChR2-flox mice. The animals were rendered hemiparkinsonian and implanted with an optic fiber at the ipsilateral external globus pallidus (GPe). Stimulation of ChR2 at striatopallidal axon terminals reduced LID and also general motility during the off L-DOPA state, without modifying the pro-motor effect of low doses of L-DOPA producing mild or no dyskinesia. Overall, the present study shows that D2-type dopamine receptors and the striatopallidal pathway modulate dyskinesia and suggest that targeting striatopallidal axon terminals at the GPe may have therapeutic potential in the management of LID.